Options for transporting Russian gas to Western Europe: A game-theoretic simulation analysis - Andreas Chollet; Berit Meinhart; Christian R. von Hirschhausen; Petra Opitz (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2001)
This paper examines the perspectives of Russian gas exports to Western Europe and the strategic options of the CIS gas transiting countries, namely Ukraine and Belarus. The development of a new transit corridor through Belarus (the Yamal-Europe pipeline), depriving Ukraine of its former monopoly, has modified the situation profoundly. The thrust of the paper is an analysis of nthe strategies that Ukraine and Belarus may pursue in transiting Russian gas: non-cooperative duopoly, cooperative duopoly, and individual or collective cooperation with Russia. Using a demand function for Western European gas imports from Russia, we estimate prices and quantities for gas transit, the expected profits for Russia, Ukraine, and Belarus, and the resulting import prices for Western Europe. The results indicate that Ukraine suffers a loss of several hundred million USD annually from the market entry of Belarus, Belarus has an incentive to increase its gas transit capacity to at least 56 billion cubic meters, and Russia's profits increase, in particular when it unites its gas sector with Belarus and Ukraine. For Western Europe, all scenarios indicate an increase in welfare through the new pipeline, but also an increasing importance of gas imports from Russia. – – Der Beitrag untersucht die Perspektiven russischer Gasexporte nach Westeuropa und die strategischen Optionen der Gastransitländer Ukraine und Belarus. Durch den Neu- und Ausbau eines Gastransitkorridors durch Belarus (die Jamal-Europa-Pipeline) geht die bisherige Monopolstellung der Ukraine als Transitland verloren. Ziel der Arbeit ist die Modellierung und Quantifizierung unterschiedlicher Wettbewerbsstrategien, wie das nichtkooperative Duopol, das kooperative Duopol, oder die individuelle bzw. kollektive Kooperation der Transitländer mit Russland. Hierfür werden Exportpreise und -mengen sowie die resultierenden Gewinne der Spieler geschätzt. Durch den Markteintritt von Belarus ergeben sich erhebliche Verluste für die Ukraine, während sich Belarus mit einem Ausbau seiner Kapazitäten auf 56 Mrd. m3 noch besser stellt. Russlands Gewinne steigen insbesondere durch die vertikale Integration der belarussischen und ukrainischen Gassektoren. Für Westeuropa legen die Ergebnisse erhebliche Wohlfahrtsgewinne durch den Pipelineausbau nahe, gleichzeitig aber auch eine gestiegene Abhängigkeit von Gasimporten aus Russland.
Keywords: Q41; L13; C71; P20; 330; Gas; pipelines; strategic behavior; CIS; Russia; Gasleitungstransport; Transit; Gebühr; Staatliche Preispolitik; Spieltheorie; Theorie; Ukraine; Weißrussland